Antenna Reconfiguration Controller for 5G Communication Systems - Ayhan Yazgan (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, an Antenna Reconfiguration Controller (ARC) is presented. This controller is an electronic circuit based on 8 bit microprocessor and can be easily placed in the communication hardware platform. Proposed controller circuit can be used to reconfigure the antenna frequency, pattern or polarization for the possible 5G communication requirements. Designed ARC has the ability of switching selected PIN diodes or optical switches in order to obtain the desired frequency bands. Frequency reconfiguration of a monopole antenna experiment has also been conducted to prove the proposed ARC reliability. According to the measurement results the monopole antenna frequency has successfully been reconfigured from 900 MHz (when the PIN diode is OFF) to 582 MHz (when the PIN diode is ON).